Literasi Digital Safety Orang Tua Peserta Didik Sekolah Dasar di Kota Tasikmalaya - Vanida Amani, - (2022)
This research is motivated by individual digital media activities, especially parents in elementary schools who still don't understand the importance of digital literacy, as in many cases there are still many people who use social media and digital media without paying attention to the security. This is contrary to the existence of digital literacy, because the main goal of digital literacy is a person understanding digital literacy so that he will be proficient in digital media and have a digital literacy. It has also been explained how to use good media that does not violate applicable rules. This study aims to determine the knowledge parents of elementary school students have on digital security. This research was conducted by following the steps of the survey research methodology, so that the data collection process was carried out using an instrument in the form of a questionnaire. The subjects in this study were parents of elementary school students in the city of Tasikmalaya, West java. Digital safety parental literacy aspects of digital security are included in good knowledge (86%), Parents digital safety literacy aspect of digital track record are very good (77%), and digital safety parental litera student Supervision aspect are in the medium category that is (35%). It can be concluded that most or many parents have a very good category of digital safety literacy.